Differential Lectin Binding Patterns Identify Distinct Heart Regions in Giant Danio (Devario aequipinnatus) and Zebrafish (Danio rerio) Hearts. (November 2016) - Manalo, Trina; May, Adam; Quinn, Joshua; Lafontant, Dominique S.; Shifatu, Olubusola; He, Wei; Gonzalez-Rosa, Juan M.; Burns, Geoffrey C.; Burns, Caroline E.; Burns, Alan R.; Lafontant, Pascal J.
Lectins are carbohydrate-binding proteins commonly used as biochemical and histochemical tools to study glycoconjugate (glycoproteins, glycolipids) expression patterns in cells, tissues, including mammalian hearts. However, lectins have received little attention in zebrafish ( Danio rerio ) and giant danio ( Devario aequipinnatus ) heart studies. Here, we sought to determine the binding patterns of six commonly used lectins—wheat germ agglutinin (WGA), Ulex europaeus agglutinin, Bandeiraea simplicifolia lectin (BS lectin), concanavalin A (Con A), Ricinus communis agglutinin I (RCA I), and Lycopersicon esculentum agglutinin (tomato lectin)—in these hearts. Con A showed broad staining in the myocardium. WGA stained cardiac myocyte borders, with binding markedly stronger in the compact heart and bulbus. BS lectin, which stained giant danio coronaries, was used to measure vascular reconstruction during regeneration. However, BS lectin reacted poorly in zebrafish. RCA I stained the compact heart of both fish. Tomato lectin stained the giant danio, and while low reactivity was seen in the zebrafish ventricle, staining was observed in their transitional cardiac myocytes. In addition, we observed unique staining patterns in the developing zebrafish heart. Lectins' ability to reveal differential glycoconjugate expression in giant danio and zebrafish hearts suggests they can serve as simple but important tools in studies of developing, adult, and regenerating fish hearts.